Analysis of consumer behavior toward organic food products in Sweden - Yadegari, Neda (SLU/Dept. of People and Society, 2022)
Organic food has attracted attention from many consumers in recent years, both in Sweden and internationally. Due to people's growing interest in sustainable production and consumption, many researchers have attempted to identify and explain the motives and barriers that influence the intention to buy and consume organic food. This study combines previous research on this topic with quantitative analysis to examine the factors that influence consumer intentions and behavior in Sweden. To understand the gap between purchase intention and behavior, as well as the motivating factors that lead consumers to purchase organic food, a conceptual model based on the Theory of Planned Behavior (TPB) was developed. The proposed model included not only all the standard relationships of the Theory of Planned Behavior but also the main motives and barriers identified in previous studies on this subject. Based on the responses from 110 Swedish consumers, the analysis using descriptive statistics, regression, ANOVA, reliability, and factor analysis shows that purchase intention and perceived behavioral control influence Swedish consumers' organic food purchase behavior, with intention having the strongest influence on behavior. Attitude has a strong influence on consumers' intention to buy organic food, followed by subjective norms and perceived behavioral control. The results also indicate that perceived environmental benefits, perceived health benefits, and good taste are the main motivational factors that lead to consumers' positive attitudes toward organic food and increased purchase intention for organic food. The two barriers, the perceived price of organic food and consumer purchasing habits, are the most important barriers that cause the gap between behavior and intention to widen. Academic and managerial implications are presented based on the findings of this study.